2008
DOI: 10.1158/0008-5472.can-08-0984
|View full text |Cite
|
Sign up to set email alerts
|

Deleted in Liver Cancer 1 Controls Cell Migration through a Dia1-Dependent Signaling Pathway

Abstract: Deleted in liver cancer (DLC) 1 and 2 are Rho GTPaseactivating proteins that are frequently down-regulated in various types of cancer. Ectopic expression in carcinoma cell lines lacking these proteins has been shown to inhibit cell migration and invasion. However, whether the loss of DLC1 or DLC2 is the cause of aberrant Rho signaling in transformed cells has not been investigated. Here, we have down-regulated DLC1 and DLC2 expression in breast cancer cells using a RNA interference approach. Silencing of DLC1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 39 publications
4
41
1
Order By: Relevance
“…Thus, deregulation of Rho activity is involved in oncogenic transformation of cells. 34 Accumulating evidence has recently indicated that DLC1 may act as a tumor suppressor by inhibiting Rho signaling. Moreover, loss of DLC1 expression has been clinically detected in many types of human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, deregulation of Rho activity is involved in oncogenic transformation of cells. 34 Accumulating evidence has recently indicated that DLC1 may act as a tumor suppressor by inhibiting Rho signaling. Moreover, loss of DLC1 expression has been clinically detected in many types of human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Fast kinetics (Ͻ1000 s) were performed with a Hi-Tech Scientific SF-61 stopped-flow instrument with a mercury xenon light source and TgK Scientific Kinetic Studio software (version 2. 19). An excitation wavelength of 545 nm was used for tamra.…”
Section: Constructs-humanmentioning
confidence: 99%
“…However, little is known about the molecular mechanisms through which DLC family proteins are capable of suppressing cell motility and cell growth. In their study, Holeiter et al have shown that enhanced migration of cells lacking DLC1 is dependent on the Rho effector protein Dia1 and does not require the activity of Rho kinase (ROCK) (64). Leung et al provide evidence for a key mechanism through which DLC proteins act as tumor suppressors (65).…”
Section: Dlcs Act As Tumor Suppressor Genesmentioning
confidence: 99%